An empirical analysis of home equity loan and line performance - Agarwal, Sumit; Ambrose, Brent W.; Chomsisengphet, Souphala; Liu, Chunlin (Journal of Financial Intermediation, 2006)
Given the growth in home equity lending during the 1990s, it is imperative that lenders and regulators understand the risks associated with this segment of the residential mortgage market. Using a unique panel data set of over 135,000 homeowners with second mortgages, our analysis indicates that significant differences exist in the prepayment and default probabilities of home equity loans and lines, providing insights into bank minimum capital requirements. We find that households with equity loans are relatively more sensitive to changes in interest rates. By contrast, households with equity lines are more sensitive to appreciation in property value.